2010
DOI: 10.1371/journal.pone.0013913
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Herbivory Interactively Drive Coral-Reef Recovery Patterns in American Samoa

Abstract: BackgroundCompared with a wealth of information regarding coral-reef recovery patterns following major disturbances, less insight exists to explain the cause(s) of spatial variation in the recovery process.Methodology/Principal FindingsThis study quantifies the influence of herbivory and water quality upon coral reef assemblages through space and time in Tutuila, American Samoa, a Pacific high island. Widespread declines in dominant corals (Acropora and Montipora) resulted from cyclone Heta at the end of 2003,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…While a limited number of previous studies showed that nutrients can drive macroalgal production in some locations (Smith et al 2001;Lapointe et al 2004;Littler et al, 2006a), the majority of field experiments identified herbivory as the key controlling factor for algal growth (Miller et al 1999;Thacker et al 2001;Belliveau and Paul 2002;Diaz-Pulido and McCook 2003;McClanahan et al 2003;Sotka and Hay 2009;Burkepile and Hay 2009;Rasher et al 2012;. The conflicting results from field experiments may be due to complex interactions between herbivory and nutrients that may vary with productivity, latitude, algal group and duration of study (Burkepile and Hay 2006;Houk et al 2010;Smith et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a limited number of previous studies showed that nutrients can drive macroalgal production in some locations (Smith et al 2001;Lapointe et al 2004;Littler et al, 2006a), the majority of field experiments identified herbivory as the key controlling factor for algal growth (Miller et al 1999;Thacker et al 2001;Belliveau and Paul 2002;Diaz-Pulido and McCook 2003;McClanahan et al 2003;Sotka and Hay 2009;Burkepile and Hay 2009;Rasher et al 2012;. The conflicting results from field experiments may be due to complex interactions between herbivory and nutrients that may vary with productivity, latitude, algal group and duration of study (Burkepile and Hay 2006;Houk et al 2010;Smith et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Available studies have rarely assessed the importance of these controls on reefs with varying levels of anthropogenic influence (Rasher et al 2012). However, such studies are needed to better evaluate the context dependency of bottom-up versus top-down effects (Houk et al 2010;Smith et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are limited insights for identifying when thresholds may be crossed, in a setting with interactive, and cumulative impacts of multiple stressors, which often result in spurious and confounding effects [2], [24]. In addition, a system's response to stressors can adopt various linear and non-linear complex behaviour patterns, which for modelling purposes can be represented in many forms of fuzzy logic membership functions including trapezoidal, sinusoidal, logistic, Gaussian etc [2], [48].…”
Section: Introductionmentioning
confidence: 99%
“…While self-reinforcing mechanisms are driving harvest volumes up, many desirable reef fish are known to have slow growth and late reproductive maturation (Choat et al 1996;Birkeland 2004;Heupel et al 2010). The consequences of ensuing fishery depletions include reduced ecological functions and altered trophic structures that threaten coral-reef integrity and resilience (Folke et al 2004;Cinner and McClanahan 2006;Houk et al 2010), as well as social structure (Costanza et al 1997;Brander et al 2007).…”
Section: Introductionmentioning
confidence: 99%